Application of Pogil Learning Model Integrated with Local Wisdom to Improve Students' Critical Thinking Skills - Izza, Zumrotul; Haryanto, Sri; Firdaus, Firdaus (Universitas Islam Negeri (UIN) Mataram, 2024)
This article aims to: 1) Know whether students who learn using the POGIL Learning Model integrated with local wisdom have better critical thinking skills than students who learn with conventional learning. 2) Knowing how much the improvement of students' critical thinking skills in the application of the POGIL Learning Model integrated with local wisdom. This article uses a quantitative approach. The method used is Quasi Experiment Design. This study used a pretest-postest control group design. Data analysis techniques were carried out by analyzing preliminary tests of normality and homogeneity then hypothesis testing and N gain testing using the SPSS program. The results of this study showed the following: 1) The results of the first hypothesis test, namely the independent t test, obtained the results of the price of thit > ttab , namely 2.156>1.671 so that H0 is rejected and Ha is accepted, it can be concluded that critical thinking skills are higher in the experimental class using the POGIL learning model integrated with local wisdom. 2) The second hypothesis test using the N-Gain test obtained the results of the experimental class the average value of the N-gain score for the experimental class (POGIL model) after and before being treated was 57.380 or 57.4% and had an N-gain criterion value of 0.4970 included in the medium criteria and was quite effective.